The spatiotemporal evolution of flight-coupled wind field for a four-rotor plant protection unmanned aerial vehicle - Fengbo Yang; Zhiwei Li; Guangyao Zhang; Hongping Zhou (PLoS ONE, 2025)
The four-rotor plant protection Unmanned Aerial Vehicle (UAV) is an important piece of equipment for the efficient plant protection field. However, the flight-coupled wind field is unclear, which has become the bottleneck factor limiting the improvement of the spray quality. When the multi-rotor plant protection UAV flew and sprayed, the liquid droplets were accelerated, the stems and branches were shaken, and the leaves were turned over in the disturbance area of the spiral backward flight-coupled wind field. The flight-coupled wind field, liquid droplets and crop canopy were closely related. Only when the flight-coupled wind field was analyzed could the interaction mechanism among the flight-coupled wind field, liquid droplets, and crop canopy be effectively studied, then the flight and spray scheme could be reasonably formulated. By combining the Re-Normalization Group (RNG) k-ε turbulence model, compressible Reynolds Averaged Navier-Stokes (RANS) equation, the dynamic mesh based on the spring smoothing and layering method, pressure-velocity coupling algorithm, a computational fluid dynamics (CFD) model of the flight-coupled wind field for the four-rotor plant protection UAV was established, the dynamic evolution law of the flight-coupled wind field in the spatial and temporal dimensions was also discussed in this paper. Numerical simulations were carried out for flight-coupled wind fields in two working conditions, analysis showed that the maximum relative error between the simulated and measured values of Zb-direction (Z direction in the absolute coordinate system) velocity was less than 12.7% when the flight-coupled wind field was stable. When switching from hover to flight state, the downwash wind field experienced a lateral interruption and developed into the stable flight-coupled wind field after flying for 0.696 s, and the velocity distribution diagram of the cross section evolved from four rings to four horseshoe vortices. When the flight-coupled wind field evolved to stabilize, the dense atmosphere reduced the absolute values of the four Zb-direction velocity peaks at observation line 1 from left to right along the flight direction by 4.5%, 4.2%, 9.0%, and 26.1% respectively. The angles between the horizontal direction and the four curves formed by Zb-direction velocity peaks were also changed from 90° to 72°, 69°, 61°, and 56° respectively at the flight speed of 3 m/s. Therefore, the installation of the nozzle and the formulation of the spray strategy are crucial to improve the spray deposition effect.